Ethnographic Method - Alharbi , Salwa S. (Advances in Social Sciences Research Journal, 2019)
The paper lays forth a historical background about the ethnographic esearch method and how it developed. Ethnography’s purpose was the examination of a wide range of diverse cultural groups, the value of which not only enhances one’s own experience relative to specific cultural traditions, but such comprehension also aids in the development of a much deeper appreciation for what transpires in other cultures and traditions. Supported by review of literature, the paper concludes that the point of this method is not to judge a certain culture, but to understand the subject’s culture the way the natives understand it.